FORMATION OF TOOLS FOR MANAGEMENT OF RESOURCE PROVISION OF INDUSTRIAL ENTERPRISES' ACTIVITIES FROM THE POSITION OF THEIR ECONOMIC SECURITY (Development Service Industry Management, 2025)
This article is devoted to the study of the essence of resource support of the enterprise's activities and its management. Resource support is a set of financial, material, information or human resources, as well as processes that include planning, attracting, distributing, using and controlling the enterprise's resources. The paper analyzes the main components of the enterprise's resource potential: production component, resource-raw material, intangible, technical-technological, infrastructure, intellectual-human, financial-investment, marketing, scientific-technical, information and environmental components. The toolkit for managing the resource support of an industrial enterprise and its significance for the economic security of the enterprise is determined. Such toolkit includes: organizational, managerial, production and information and communication tools. It has been established that the formation of an effective toolkit for managing the resource support of the activities of industrial enterprises contributes not only to ensuring effective and stable economic activity, but also to the implementation of the enterprise's economic security strategy. In addition, the toolkit ensures the security of all components of the resource potential of an industrial enterprise, the stability of all business processes of the enterprise, the minimization of risks and threats associated with the limitation or absence of one of the components of the resource potential, the competitiveness of the enterprise and its products in the domestic and foreign markets, support for the investment potential of the industrial enterprise, the adaptability of the enterprise to market changes, the protection of the components of the economic security of the industrial enterprise and the formation of opportunities for the development of the industrial enterprise.
Keywords: resource provision; resource potential; industrial enterprise; economic security; management tools